Anaerobic digestion technology in poultry and livestock waste treatment - a literature review - Sakar, Suleyman; Yetilmezsoy, Kaan; Kocak, Emel (SAGE PUBLICATIONS LTD, 2009)
A literature review has been undertaken to investigate the performance of the different anaerobic process configurations and operational conditions used in poultry and livestock waste treatment. The results of the extensive literature review showed that a wide range of different reactor volumes varying from 100 mL to 95 m(3) were utilized in the investigation of anaerobic processing of poultry manure. Retention times studied were between 13.2 h and 91 days. Most of studies were carried out under mesophilic conditions maintained between 25 and 35 C. Chemical oxygen demand ( COD) removals and organic loading rate (OLR) ranged from 32 to 78%, and from 1.1 to 2.9 kg COD m(-3) day(-1), respectively. Biogas yields were achieved between 180 mL g(-1) COD added and 74 m(3) day(-1) for a wide range of different reactor configurations. Up-flow anaerobic sludge blanket (UASB) seems to be a suitable process for the treatment of poultry manure wastewater and the liquid fraction of hen manure, due to its ability to maintain a sufficient amount of active biomass. The literature review showed that various reactor configurations such as fixed-film reactor, attached-film bioreactor, anaerobic rotating biological reactor, batch reactors, downflow anaerobic filter, fixed dome plant, UASB, continuously stirred tank reactor (CSTR), up-flow anaerobic filter (UAF), temperature-phased anaerobic digestion (TPAD), anaerobic hybrid reactor (AHR), and two-stage anaerobic systems are well suited to anaerobic processing of cattle manure. At both mesophilic and thermophilic conditions, high COD removals (87-95%) were achieved for treatment of cattle manure wastewaters. The COD and volatile solids ( VS) reductions obtained were 37.9 to 94% and 9.6 to 92%, respectively. During the studies, OLR and retention times ranged between 0.117 and 7.3 g VS L-1 day(-1) and between 0.5 and 140 days, respectively. In anaerobic processing of cattle manure, methane yields between 48 mmol CH4 L-1 and 4681.3 m(3) CH4 month(-1) were found for the corresponding reactor volumes of 120 mL and 1300 m(3), respectively. In anaerobic processing of swine manure, OLR ranged from 0.9 to 15.42 g VS L-1 day(-1) at mesophilic conditions (25-35 degrees C). The reactor volumes varied between 125 mL and 380 L. Temperature and retention times ranged from 25 to 60 degrees C, and 0.9 to 113 days, respectively. COD and VS reductions achieved were between 57 and 78% and between 34.5 and 61%, respectively. Moreover, methane yields were obtained between 22 and 360 mL CH4 g(-1) VS added. The results showed that UASB, anaerobic baffled reactors, CSTR, and anaerobic sequencing batch reactor (ASBR) were successfully utilized in anaerobic processing of swine manure at both mesophilic and thermophilic conditions.
Keywords: Poultry manure; livestock manure; anaerobic digestion; hydraulic retention time; biogas; wmr 1167-6; SCREENED DAIRY MANURE; SEQUENCING BATCH REACTOR; CATTLE MANURE; UASB REACTORS; SWINE MANURE; METHANE PRODUCTION; PIG MANURE; MICROBIAL COMMUNITY; TEMPERATURE; PERFORMANCE; Engineering; Environmental Sciences & Ecology